Revealing the Genetic Components Responsible for the Unique Photosynthetic Stem Capability of the Wild Almond Prunus arabica (Olivier) Meikle - Brukental, Hillel; Doron-Faigenboim, Adi; Bar-Ya’akov, Irit; Harel-Beja, Rotem; Attia, Ziv; Azoulay-Shemer, Tamar; Holland, Doron (Frontiers in Plant Science, 2021)
Almond (Prunus dulcis (Mill.) D. A. Webb) is a major deciduous fruit tree crop worldwide. During dormancy, under warmer temperatures and inadequate chilling hours, the plant metabolic activity increases and may lead to carbohydrate deficiency. Prunus arabica (Olivier) Meikle is a bushy wild almond species known for its green, un-barked stem, which stays green even during the dormancy period. Our study revealed that P. arabica green stems assimilate significantly high rates of CO2 during the winter as compared to P. dulcis cv. Um el Fahem (U.E.F), and may improve carbohydrate status throughout dormancy. To uncover the genetic inheritance and mechanism behind the P. arabica Stem Photosynthetic Capability (SPC), a segregated F1 population was generated by crossing P. arabica to U.E.F. Both parent’s whole genome was sequenced, and a single nucleotide polymorphism (SNP) calling identified 4,887 informative SNPs for genotyping. A robust genetic map for U.E.F and P. arabica was constructed (971 and 571 markers, respectively). QTL mapping and association study for the SPC phenotype revealed major QTL (log of odd (LOD)=20.8) on chromosome 7, and another minor but significant QTL on chromosome 1 (LOD=3.9). Finally, a list of 71 candidate genes was generated. This work sets the stage for future research to investigate the mechanism regulating the SPC trait, how it affects the tree’s physiology, and its importance for breeding new cultivars better adapted to high winter temperatures.